"Arab Spring" Analisa penyebab terjadinya revolusi di Tunisia dan Mesir tahun 2011 - , AZMAN, Drs. Samsu Rizal P. M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis discussed the cause of wave revolutions in Tunisia and Egypt in 2011, which toppled the regime that has been in power decades ago. Although many countries in North Africa and the Middle East experienced about social and political turmoil almost in the same time, but not all of them experienced in succession of government and have a great revolution as both countries above. The cause of the revolutions in those two countries became questions for many people, especially in the Islamic countries, since emerged and spread so quickly. The crush of social economic and political realities led public anger, which led to a wave of protests. Although it was in small scale in the beginning, but later extended to the whole country. The government responded the protest people with repressive measures so that make the people's anger sparked in large scale, and finally required the authorities in both countries to retreat. This thesis researched about revolutions that happened in Tunisia and Egypt starting from the causes, triggers, and supporting factors in the revolution. To find answers about the cause of the revolution, the author used two main theories in analyzing the facts in the discussion of this study, namely the theory of social change and the theory of revolution. Social change theory will answer about how the process of social change in a community and what factors caused the occur. While the theory of revolution will answer what the conditions or causes of a revolution in a society. This study also simultaneously classifies the main actors who play a role in revolutions in both countries. In conclusion, researcher found that there are two main factors that led to the revolutions in both countries, namely social economic factors and political factors. There was a very fundamental difference regarding the caused of the revolutions in both countries, which is the turmoil of the revolution in Tunisia was originated from the factor of social and economic issues, then followed by political factors. While the caused of the revolution in Egypt is the opposite, it started from the political issues and then continued with social economic factors. Revolution in both states purely initiated and driven by the general public in both countries, especially young intellectuals, media activists, workers and opposition parties that had been sequestered.